Observed Intraseasonal Oceanic Variations in the Eastern Equatorial Indian Ocean and in the Outflow Straits of the Indonesian Throughflow - Iskhaq Iskandar; Yukio Masumoto; Keisuke Mizuno (Institute for Research and Community Services (LPPM) ITB, 2010)
The observed currents in the eastern equatorial Indian Ocean and in the outflow straits of the Indonesian Throughflow (ITF) are shown to have significant intraseasonal variations and coherency during January 2004